2017
DOI: 10.1021/acs.orglett.7b00496
|View full text |Cite
|
Sign up to set email alerts
|

Macrophilone A: Structure Elucidation, Total Synthesis, and Functional Evaluation of a Biologically Active Iminoquinone from the Marine Hydroid Macrorhynchia philippina

Abstract: A previously uncharacterized pyrroloiminoquinone natural product, macrophilone A, was isolated from the stinging hydroid Macrorhynchia philippina. The structure was assigned utilizing long-range NMR couplings and DFT calculations and proved by a concise, five-step total synthesis. Macrophilone A and a synthetic analogue displayed potent biological activity, including increased intracellular reactive oxygen species levels and submicromolar cytotoxicity toward lung adenocarcinoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…The 149 new compounds reported from cnidarians in 2017 represents an approximately 30% drop below the previous decadal average. While the structures of the majority of NPs isolated from cnidarians are derived from terpene biosynthesis, a handful of nitrogenous metabolites were reported in 2017, including the cytotoxic ceramide 1218 (Cespitularia stolonifera), 533 the cytotoxic iminoquinone macrophilone A 1219 (hydroid Macrorhynchia philippina), 534 and the 2-aminoimidazole alkaloids terrazoanthines A-C 1220-1222 from the zoanthid coral Terrazoanthus onoi. 535 Of note was macrophilone A 1219 which inhibited the small-ubiquitin-like modier (SUMO) conjugation cascade, via an oxidative mechanism.…”
Section: Cnidariansmentioning
confidence: 99%
“…The 149 new compounds reported from cnidarians in 2017 represents an approximately 30% drop below the previous decadal average. While the structures of the majority of NPs isolated from cnidarians are derived from terpene biosynthesis, a handful of nitrogenous metabolites were reported in 2017, including the cytotoxic ceramide 1218 (Cespitularia stolonifera), 533 the cytotoxic iminoquinone macrophilone A 1219 (hydroid Macrorhynchia philippina), 534 and the 2-aminoimidazole alkaloids terrazoanthines A-C 1220-1222 from the zoanthid coral Terrazoanthus onoi. 535 Of note was macrophilone A 1219 which inhibited the small-ubiquitin-like modier (SUMO) conjugation cascade, via an oxidative mechanism.…”
Section: Cnidariansmentioning
confidence: 99%
“…These compounds all have a high heteroatom content and relatively few protons observable by NMR, so the total synthesis of 1 was undertaken to confirm its structure. 22 The molecular formula of macrophilone B ( 2 ) was established as C 10 H 10 N 2 O 4 S based on HRESIMS data, and this differed from the molecular formula of 1 by the addition of two oxygens and the loss of NH. The 1 H (Table 1) and 13 C NMR data (Table 2) of 2 corresponded closely with those of 1 , showing all the characteristic signals for a hydroxymethyl-substituted pyrroloiminoquinone moiety.…”
Section: Resultsmentioning
confidence: 99%
“…The 13 C NMR spectrum in CD 3 OD displayed seven nonprotonated sp 2 carbons [ δ C 167.2 (C-9), 159.6 (C-4), 144.6 (C-8a), 128.1 (C-9a), 125.5 (C-3), 121.6 (C-3a), 91.6 (C-4a)], a protonated sp 2 ( δ C 126.1, C-2), and a hydroxymethylene carbon ( δ C 55.7, C-10), which corresponded closely with the pyrroloiminoquinone skeleton of 1 . 22 Two additional methylene carbons ( δ C 43.4, C-7; 22.3, C-6) and the requirement of one more unsaturation equivalent indicated they bridged the amino and thio groups to form a 3,4-dihydro-2 H -1,4-thiazine ring. The deshielded chemical shifts of H 2 -7 ( δ H 3.86) and C-7 ( δ C 43.4) in comparison with those of H 2 -6 ( δ H 3.04) and C-6 ( δ C 22.3) suggested that C-7 was N-substituted and C-6 was S-substituted.…”
Section: Resultsmentioning
confidence: 99%
“…167 An interesting hybrid assay format is micro/nanocapillary electrophoresis (CE), which continues to be an HTS format that is frequently employed for drug discovery. 168 Improvements in the optics of both excitation and emission using LIF has allowed increasingly small reaction volumes to be deployed in the context of an HTS screening campaign. This has spurred the exploration of microuidics, or even nanouidics, in the context of high throughput drug discovery.…”
Section: Non-enzymatic Biochemical Screensmentioning
confidence: 99%